Assessment of relative abundance of Telmatobius culeus in littoral zone of Lake Titicaca, Peru - Ramos Rodrigo, Víctor Enrique (2019)
The Telmatobius culeus relative abundance and its microhabitat use was determined. In 13 areas of Peruvian littoral of Lake Titicaca was carried out, during the dry season, since June to August 2017. In each the evaluation areas, snorkeling was used to perform three 100 x 2 m transects. A total of 38 transects were evaluated. 45 individuals were registered in only six evaluation zones. The largest number of individuals were found in the North Perka area, with a relative abundance of 10.33 individuals/hour/02 people, at a depth of 1.5 m; in seven zones no individual was registered. Individuals were found in the following micro habitats: 17 were found on aquatic vegetation, 11 in sand combined with aquatic vegetation, 9 in rock combined with aquatic vegetation, 5 in mud combined with aquatic vegetation, 2 in rock and 1 in sand. At the same time, analyzes of different water quality parameters were performed in each study area, such as: temperature, pH, alkalinity, hardness and oxygen.